PEMBELAJARAN BERBASIS EDUTAINMENT UNTUK MENINGKATKAN MINAT BELAJAR PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 1 PORONG - Nuril Fatimatus Sholikh; Maskuri Maskuri; Muhammad Sulistiono (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The aims of this study are (1) to determine the edutainment method in Islamic Religious Education Learning at SMPN 1 Porong (2) to determine the application of edutainment methods in Islamic religious education learning at SMPN 1 Porong (3) to determine the results of the edutainment method in Islamic religious education learning on students' interest in learning at SMPN 1 Porong. This research uses qualitative research which is a case study. Researchers used data collection instruments with the process of observation, interviews, and documentation. The results of this study are (1) planning by preparing annual programs, planning semester programs, edutainment learning materials, planning learning processes, and compiling syllabus (2) Providing a happy atmosphere, creating a conducive learning environment, presenting relevant material, and attracting interest. in uploading the interests of students (3) Learning becomes more conducive, Students easily develop their thinking framework through the edutainment method, Students become more active in the learning process, The value of students increases